Posterior partially edentulous jaws, planning a rehabilitation with dental implants - Monteiro, Douglas Roberto [UNESP]; Silva, Emily V. F. [UNESP]; Pellizzer, Eduardo P. [UNESP]; Filho, Osvaldo Magro [UNESP]; Goiato, Marcelo C. [UNESP] (Baishideng Publishing Group Inc, 2015)
To discuss important characteristics of the use of dental implants in posterior quadrants and the rehabilitation planning. An electronic search of English articles was conducted on MEDLINE (PubMed) from 1990 up to the period of March 2014. The key terms were dental implants and posterior jaws, dental implants/treatment planning and posterior maxilla, and dental implants/treatment planning and posterior mandible. No exclusion criteria were used for the initial search. Clinical trials, randomized and non randomized studies, classical and comparative studies, multicenter studies, in vitro and in vivo studies, case reports, longitudinal studies and reviews of the literature were included in this review. One hundred and fifty-two articles met the inclusion criteria of treatment planning of dental implants in posterior jaw and were read in their entirety. The selected articles were categorized with respect to their context on space for restoration, anatomic considerations (bone quantity and density), radiographic techniques, implant selection (number, position, diameter and surface), tilted and pterygoid implants, short implants, occlusal considerations, and success rates of implants placed in the posterior region. The results derived from the review process were described under several different topic headings to give readers a clear overview of the literature. In general, it was observed that the use of dental implants in posterior region requires a careful treatment plan. It is important that the practitioner has knowledge about the theme to evaluate the treatment parameters. The use of implants to restore the posterior arch presents many challenges and requires a detailed treatment planning.
Keywords: Dental implants; Edentulous jaw; Mandible; Maxilla; Treatment